Reaksi sarjana Turki terhadap sains, teknologi dan modeniti pada abad ke-19 hingga awal abad ke-20 / Fadhilah Mustapha - Fadhilah , Mustapha (2021)
The Ottoman Empire, the greatest and longest ruling Muslim empire in history, began to face enormous threats from the West even before the 17th century. In the beginning of the 17th century, the Ottomans were behind the West in the advancement of science and technology. Beginning from its defeat in Vienna in 1683, the Ottoman lost some of its provinces due to defeats in various battles. Realizing the widespread of western power, the Ottomans took steps to reinforce its power through several attempts, which include the transmission of science and technology from the West through the two main channels, which are the establishment of military, medical and higher educational institutions and translation activities by scholars. As a result, the Ottomans were exposed with the Western’s ideas which lead to the emergence of those with inclination towards the Western’s system of thought and belief, despite its contrary with their culture and religion. This situation creates mixed reactions from different scholars. The objective of this study is threefold. Firstly, is to study the transmission of Western science and technology into the Ottoman Empire in the 19th and early 20th century. Secondly, it attempts to study the form of reactions shown by the Turkish Ottoman scholars in their writings towards the acceptance of Western’s ideas in science and technology, and lastly to compare the different forms of reaction. In order to meet the objectives of the research, an analysis was concluded based on the data obtained during two week fieldwork conducted in Istanbul and the ideas written by the scholars in their writings. The findings show that some Turkish Islamic scholars are selective towards the ideas in science and technology pioneered by the West while some others either accept or reject totally any element of Western’s science and technology. Their ideas are then classified into related themes. This study focuses only on the developments occurred in the 19th and early 20th century, hence it propose that further studies to be conducted to examine the impacts of scientific and technological developments in Turkey after it became a republic.